The exploration of self-perception in the educational attainment of high achieving students from a low socioeconomic background in South African - Sebele, Phemelo Berveley (University of the Witwatersrand, Johannesburg, 2023)
Background: The achievement gap between students’ from lower-and-higher socioeconomic backgrounds is a global challenge that continues to widen. Education inequalities persist more widely with students from low socioeconomic backgrounds who are more likely to drop out of compulsory high school. However, individual characteristic such as resilience, growth-mind and positive self-concept – though largely studied using survey based methods - have been found to lessen the achievement gap. Yet, the influence of such psychological factors, specifically, self-perception as an overarching concept, is poorly understood, especially in low-to-middle income contexts like South Africa. Aim: This study aimed to understand the lived experiences and processes involved in self-perception of high-achieving first year university students from a low-socio-economic background in the low-to-middle income context of South Africa. Methods: An ecological systems theory and phenomenological approach guided this study. Semi-structured interviews, incorporating retrospective (high school) and current (university) questions, were conducted with 12 first-year university students. Findings: The research demonstrated that the lived experiences of self-perception in high achieving students’ that come from a low SES background are both individualised and similar. The findings revealed that validation which was distributed between internal (self-belief) and external (affirmations from external sources) played a significant role in the students’ academic success. Furthermore, the data also demonstrated that the perception of intelligence is largely influenced by what the students’ observe from their different environments. Conclusion: This study adds to our understanding of the role of self-perception in educational inequality which can be used in future school-based, family and wider policy interventions. It further demonstrates the need to understand these complex relationships by drawing on lived experience of students using qualitative approaches.
A Research Report Submitted in partial fulfilment of the requirements for the Degree of Master of Arts in Psychology by Coursework and Research Report in the Department of Psychology, School of Human and Community Development, Faculty of Humanities at the University of the Witwatersrand, Johannesburg, 2023.
Keywords: Self-perception; Low-to-middle income country; Academic achievement; Socio-economic status; Education inequality; UCTD; SDG-3: Good health and well-being